Ethnomathematics: Mathematical Concepts in Palm Oil Weaving Crafts - Aulia Hanifah Ahmad; Suci Dahlya Narpila (Urogram Studi Pendidikan Matematika, Universitas IVET, 2023)
The purpose of this study was to explore ethnomathematics in the woven craft of oil palm sticks. This research is qualitative research with an ethnomathematical approach. Data collection instruments use observation sheets, interview sheets, and field notes. The subjects of the study were the owner of the She Creaf production house and some of its employees. The data analysis technique used is data triangulation. The results of this study show that there are mathematical concepts found in the woven craft of oil palm sticks. The mathematical concepts found in the woven craft of oil palm weaving are measuring, calculating, set, comparison, relation, function, and according. Keywords: ethnomathematics, palm oil weaving